A multipurpose compound dor protective coatings - Del Amo, Delia Beatriz (2008)
International regulations concerning the protection of both the environment and industrial workers have prompted paint manufacturers and end users to look for suitable replacements for traditional pigments. One of the aims of this investigation was to study the inhibitive properties of ferric benzoate-based paints in simulated marine corrosion condition (3% NaCl solution). Anticorrosive paints containing ferric benzoate were formulated and their performance was evaluated by accelerated (salt fog chamber) and electrochemical (corrosion potential and ionic resistance) tests. In addition, the action of ferric benzoate as a probable antifouling agent was studied through laboratory tests and marine exposure. Ferric benzoate hydrolyzes in seawater producing a pH decrease. In this sense, the effects of the pH and the anion benzoate dissolved in seawater and leached from an antifouling paint were evaluated on Balanus amphitrite nauplii. Although benzoate anion showed an intense narcotic effect on nauplii, the results of this research clearly demonstrated that the antifouling activity is due to the combined action of this anion and the pH decrease, i.e. there exists a synergic effect. Field trials confirmed laboratory assays; paints containing ferric benzoate were effective for inhibiting organism settlement and as corrosion of metal.